Perlindungan Anak yang Berhadapan dengan Hukum (ABH) dalam Perspektif Hukum dan HAM - Nicken Sarwo Rini (Badan Strategi Kebijakan Hukum, 2013)
Related efforts to provide protection for children in conflict with the law, juvenile justice system should be interpreted broadly. It should not be only interpreted merely as handling children in conflict with the law. As a country that has ratified the Convention on the Rights of the Child, the state has a general obligation (generic obligation) to respect, protect and fulfill the rights of children without exception. By mixing up children with adults in detention or imprisonment facility will put the childs in a vulnerable situation and become victims of violence. Arguably, legal certainty-based restorative justice should be the goal of the administration of juvenile justice. The concept of restorative justice should be applied directly against any criminal acts precedes the minor offender gets proceed before the criminal court.